Entre Etnologia e Arqueologia: o universo tapajônico de Curt Nimuendajú - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2024)
The research analyzes the article “Os Tapajó”, by Curt Nimuendajú (1883-1945), published posthumously by the Museu Paraense Emílio Goeldi in 1949 and based on an important set of documentary and archaeological sources from the Lower Amazon (PA). The text is the first written by an ethnologist about this indigenous group and was the result of an expedition carried out by Nimuendajú to Santarém (PA) and surrounding areas in 1923, with funding from the Gothenburg Museum, to collect archaeological and ethnographic material. The dissertation concludes that the ethnologist's intellectual production on the Tapajó, as well as being relevant to the History of Science in Brazil, outlined a theme of archaeological studies that would be widely developed in the second half of the 20th century and configured an interpretative key on the subject that would last for decades.
Keywords: Amazônia; Produção Intelectual; Tapajó; CNPQ::CIENCIAS HUMANAS